2017
DOI: 10.1016/j.yebeh.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

An Australian nationwide survey on medicinal cannabis use for epilepsy: History of antiepileptic drug treatment predicts medicinal cannabis use

Abstract: Epilepsy Action Australia conducted an Australian nationwide online survey seeking opinions on and experiences with the use of cannabis-based products for the treatment of epilepsy. The survey was promoted via the Epilepsy Action Australia's main website, on their Facebook page, and by word of mouth. The survey consisted of 39 questions assessing demographics, clinical factors, including diagnosis and seizure types, and experiences with and opinions towards cannabis use in epilepsy. A total of 976 responses me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 39 publications
(46 reference statements)
4
73
0
1
Order By: Relevance
“…Subsequently, 142 records were screened in full‐text format, with 92 records meeting the eligibility criteria (Appendix ). Of these, 25 records corresponded to 23 unique published studies (four RCTs, 19 NRSs). An additional 33 records corresponded to trial registration records in ClinicalTrial.gov without reported results, and 34 corresponded to conference abstracts.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 142 records were screened in full‐text format, with 92 records meeting the eligibility criteria (Appendix ). Of these, 25 records corresponded to 23 unique published studies (four RCTs, 19 NRSs). An additional 33 records corresponded to trial registration records in ClinicalTrial.gov without reported results, and 34 corresponded to conference abstracts.…”
Section: Resultsmentioning
confidence: 99%
“…3 However, the uptake of prescribed medical cannabis has been limited amid caution from medical professional groups. 4,5 Community support for prescribed medical cannabis continues to grow, 6 possibly influenced by media reporting; surveys of patients with chronic pain, 7 cancer, 8 and epilepsy 9 have found that considerable numbers of Australians have either used (10e20%) or would consider using cannabis products for therapeutic purposes. However, knowledge of the unregulated use of medical cannabis in Australian remains imprecise because it is generally illegal.…”
mentioning
confidence: 99%
“…Previous studies investigating various forms of cannabis as an adjunct with anti‐epileptic medicines have reported improvements in seizure control and a reduction in frequency of seizures . However, these cannabis products often include THC and may not be suitable for patients with epilepsy because of its psychoactive effects .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…On reviewing the published literature in detail, we found 3 previously published case reports over the last two decades, detailing 4 patient cases of adults using cannabis to reduce uncontrolled seizures . We also found 1 case series study, 7 RCTs, 1 observational study and 5 surveys examining the efficacy and safety of cannabis use in epilepsy. (Table S1) These studies showed a reduction or complete freedom from seizures following the use of CBD compared with placebo.…”
Section: Case Descriptionmentioning
confidence: 99%